Application of Murottal Al-Quran Therapy on The Hallucination Scores of Hearing Hallucination Patients in Dr. RM. Soedjarwadi Psychiatric Hospital Klaten - Fihudha, Ganis Dina; Mulyaningsih (Al-Hijrah Indonesia, 2024)
Background: Auditory hallucinations are hallucinations that would listen to voices and could threaten the patient in giving commands. In schizophrenic patients with hallucinations experience auditory hallucinations by 70%, then those with visual hallucinations are found by 20% and those with sense of smell and shuttle hallucinations are 10%. Purpose: To find out how the implementation of surah al-rahman's audio therapy (surah ar-rahman) against the score of patient auditory hallucinations in Dr. RM. Soedjarwadi Psychiatric Hospital Klaten. Methods: using descriptive methods with a case study design approach, the respondents used as many as 2 patients with auditory hallucinations. For respondents to the criteria of inclusion and inclusion, the Quran's audio marital therapy takes 20 minutes out of 3 days, the scale auditory higher rating (AHRS). Results: The hallucination scores for both respondents before and after being given audio murottal Al-Quran therapy decreased, namely from moderate hallucinations to mild hallucinations. Conclusion: There was a decrease in the hallucination score after being given Audio Murottal Al-Quran therapy from moderate to mild.